Character Strength pada Atlet Penyandang Tuna Daksa di NPCI (National Paralympic Committee Indonesia) Kota Padang - Rizqa Amalia Hendri; Isna Asyri Syahrina; Andhika Anggawira (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of this study was to describe the Character Strength on the physically disabled athletes in NPCI (National Paralympic Committee Indonesia) Kota Padang. The method used mix method which are combine both quantitative and qualitative approaches. Sampling in this study using purposive sampling technique. The sample in this study was 10 athletes with physical disabilities in NPCI Kota Padang. The measuring instrument used in this study is the character strength scale which is based on the classification of character strength, namely wisdom and knowledge, courage, humanity, justice, temperance and transcendence.Character strength can be seen from the measurement result using a scale consisting of 81 items in the form of a likert scale. After that, an interview was conducted with the subject to identify more deeply related to their character strength. The result of measurements and interviews show that athletes with physical disabilities in NPCI Kota Padang have five character strength. The five character strength are appreciation, spirituality, hope, gratitude and vitality.